Relasi Harmonis Antar Umat Beragama Perspektif Al-Qur'an - bt Abdul Rahman, Waheeda (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2021)
This article aims to discuss how the stability of relations between religious communities can be well and harmoniously established. The method used in this study is a qualitative method with the type of library research. The collected data is described and then analyzed. This article concludes that harmonious relationships can be created by helping each other, caring for each other, having high empathy and sensitivity to others, Muslim or non-Muslim. Tolerance between religious communities is interpreted as an attitude to be able to live with people of other religions, by having the freedom to carry out their respective religious principles (worship), without any coercion and pressure. Inter-religious harmony can be interpreted as a condition of relations between religious communities based on tolerance, mutual understanding, mutual respect, respect for equality in the practice of their religious teachings and cooperation in the life of society, nation and state.